Occurrence of certain microfungi on reindeer pastures in northern Finland during winter 1996-97 - Jouko Kumpula; Päivi Parikka; Mauri Nieminen (Rangifer, 2000)
Thick snow covering on warm and unfrozen soil in late autumn is believed to promote mould growth on the winter pastures of reindeer. Natural feed containing potential mycotoxins is suggested to affect the condition and health of the reindeer. During this kind of winter and spring 1996-97 we collected 30 samples from winter forage plants on three winter ranges in nothern Finland. We identified altogethet 12 different species or species groups of fungi in plant samples. Most microfungi were found when the soil temperatute under the snow in winter was above 0 °C and when the snow was just melted in spring. Abundant fungi wete Mortierella spp., Pénicillium spp. and Trichoderma viride. Without exception T. viride was, the most abundant when the temperature under the snow was above 0 °C and the soil was unfrozen, and Pénicillium spp. when temperature was below zero and the soil was frozen. Mortierella spp. was abundant in both circumstances. These three fungi or genera were also abundant in samples just after snow melting in spring. Reindeer seemed to avoid digging in the places where fungi were the most abundant. Several Pénicillium species and T. viride are known to be able to produce mycotoxins. Many symptoms observed among reindeer grazing on natural pastures were quite similar to those caused by mycotoxins. Potential mycotoxins on reindeer pastures and their effects on teindeer, should be studied in mote detail.